Effective cloth folding trajectories in simulation with only two parameters - De Gusseme, Victor-Louis; wyffels, Francis (Frontiers in Neurorobotics, 2022)
Robotic cloth folding remains challenging for robots due to its highly deformable nature. In order to deal with these deformations, several strategies with varying amounts of adaptability have been proposed. We study robotic cloth folding by simulating and evaluating a trajectory search space with only two parameters: one parameter for the trajectory's height and one parameter to tilt it. We extensively analyzed folding a long-sleeved shirt in a high-fidelity simulator. To demonstrate that the trajectory is sufficiently adaptable and robust, we test several cloth shapes, cloth materials, an entire folding sequence and different folding velocities. We can deal with every folding scenario by tuning the two parameters correctly. The trajectories' simplicity and their robustness in simulation make them ideal candidates for future transfer to real-world robotic setups.